2013
DOI: 10.1097/jto.0b013e318282709c
|View full text |Cite
|
Sign up to set email alerts
|

Phase II Study of Docetaxel in Combination with Everolimus for Second- or Third-Line Therapy of Advanced Non–Small-Cell Lung Cancer

Abstract: We conducted a phase II study of docetaxel in combination with everolimus, a mammalian target of rapamycin (mTOR) inhibitor, for salvage therapy of advanced non–small-cell lung cancer (NSCLC) based on promising preclinical and early-phase clinical data. Patients with advanced-stage NSCLC treated with one or two previous systemic therapy regimens were given docetaxel (60 mg/m2) and everolimus (5 mg orally once daily on days 1–19) every 3 weeks. Archived tumor specimens were evaluated for markers of mTOR pathway… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(20 citation statements)
references
References 9 publications
1
19
0
Order By: Relevance
“…everolimus) are potent allosteric inhibitors of mTOR (Legrier et al, 2007). RAD001 is well tolerated but shows limited antitumor activity in patients with lung cancer (Besse et al, 2014; Ramalingam et al, 2013; Tarhini et al, 2010). Previous reports indicate that expression of Bcl2 is associated with resistance of cancer cells to mTOR inhibitors (Aguirre et al, 2004; Majumder et al, 2004).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…everolimus) are potent allosteric inhibitors of mTOR (Legrier et al, 2007). RAD001 is well tolerated but shows limited antitumor activity in patients with lung cancer (Besse et al, 2014; Ramalingam et al, 2013; Tarhini et al, 2010). Previous reports indicate that expression of Bcl2 is associated with resistance of cancer cells to mTOR inhibitors (Aguirre et al, 2004; Majumder et al, 2004).…”
Section: Resultsmentioning
confidence: 99%
“…It is possible that Bcl2 expression induced by mTOR inhibitor therapy may negatively affect the efficacy of mTOR inhibitor in lung therapy. This may help explain why RAD001 only had limited efficacy in lung cancer patients (Ramalingam et al, 2013; Tarhini et al, 2010). Our findings provide a strong rationale to propose that combined Bcl2 and mTOR inhibition should have superior therapeutic benefits over each agent alone.…”
Section: Discussionmentioning
confidence: 99%
“…However, a phase II study on everolimus plus gefitinib in patients with stage IIIB/IV NSCLC demonstrated that the response rate failed to meet the expected values 25 % [72]. A phase II study showed that the combination of docetaxel with everolimus increased disease control rate by 61 % and the median overall survival by 9.6 months in patients with advanced-stage NSCLC [73]. However, the combination of everolimus and erlotinib failed to show sufficient efficacy according to predefined study criteria and increased the severity of toxicity in patients with advanced NSCLC during phase II clinical study [74].…”
Section: Allosteric Inhibitors For Lung Cancermentioning
confidence: 91%
“…Also, BDA-366 efficiently suppressed growth of small-cell lung cancer tumors in a patient-derived xenograft (SCLC PDX) mouse model at the dose of 20 mg/kg for 2 weeks. Moreover, combination of BDA-366 and an mTOR inhibitor RAD001 was explored given that expression of Bcl-2 is associated with resistance of cancer cells to mTOR inhibitors such as RAD001, which displays limited antitumor activity in patients with lung cancer [57,58]. Nu/Nu mice with non-small-cell lung cancer (NSCLC, i.e.…”
Section: Non-peptide Small-molecule Inhibitors: Bda-366mentioning
confidence: 99%